ANALISIS PENGARUH FAKTOR-FAKTOR PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS KESEHATAN KOTA PROBOLINGGO - Imam Suliyono (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
The purpose of this study is to determine the effect of training factors, which consist of training materials, training institutions, training instructors and trainees on the performance of employees of Probolinggo City Health Office and know the dominant training factors affect the performance of employees of Probolinggo City Health Office. The population in this study is all employees of Probolinggo City Health Office. The implementing officer and the head of the field or sub-field are asked to answer the questionnaire about the training factors, while the employee's performance is judged based on the perception of the superior on the performance and performance of his subordinate employees on a day-to-day basis. In addition to the data obtained from the questionnaires, this study also uses personal data information of each respondent, education history, training, employment and employee grade, information obtained from the organization's archives and interviews and direct observation to the research object. The sampling technique used is the sampling with a disproportionate strafikasi, meaning that researchers can set their own number of sample members to be taken from each part with respect to uniformity of the characteristics of the population.